Novel challenges in spinal muscular atrophy: How to screen and whom to treat? - Saffari, Afshin; Kölker, Stefan; Hoffmann, Georg F.; Weiler, Markus; Ziegler, Andreas (Annals of Clinical and Translational Neurology, 2019)
In recent years, disease-modifying and life-prolonging therapies for spinal muscular atrophy (SMA) have been developed. However, patients are currently diagnosed with significant delay and therapies are often administered in advanced stages of motor neuron degeneration, showing limited effects. Methods to identify children in presymptomatic stages are currently evaluated in newborn screening programs. Yet, not all children develop symptoms shortly after birth raising the question whom to treat and when to initiate therapy. Finally, monitoring disease progression becomes essential to individualize management. Here, we review the literature on screening approaches, strategies to predict disease severity, and biomarkers to monitor therapy.
First published: 13 November 2018
Gesehen am 14.05.2019